2015
DOI: 10.1007/s10865-015-9676-8
|View full text |Cite
|
Sign up to set email alerts
|

Body awareness and pain habituation: the role of orientation towards somatic signals

Abstract: Although body awareness and pain perception are considered to be parts of the interoceptive system, the relationship between them is unclear. This study examines the association between body awareness and pain habituation, hypothesizing that this association is moderated by pain catastrophizing and mindfulness. Sixty subjects received a mildly aversive electrical stimulus for 60 s, during which they were requested to rate the amount of perceived pain. Complete habituation was indicated by abolition of pain sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 81 publications
0
27
0
Order By: Relevance
“…Phenomena such as interoceptive awareness and somatic hypervigilance are widely investigated in somatoform and anxiety disorders (Ginzburg et al., ; White, Craft, & Gervino, ; Witthöft, Basfeld, Steinhoff, & Gerlach, ). The proposed framework leads us to suggest that these somatic phenomena may be best characterized as a type of maladaptive RT.…”
Section: The Defining Features Of Maladaptive Rtmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenomena such as interoceptive awareness and somatic hypervigilance are widely investigated in somatoform and anxiety disorders (Ginzburg et al., ; White, Craft, & Gervino, ; Witthöft, Basfeld, Steinhoff, & Gerlach, ). The proposed framework leads us to suggest that these somatic phenomena may be best characterized as a type of maladaptive RT.…”
Section: The Defining Features Of Maladaptive Rtmentioning
confidence: 99%
“…These sensations may include pain or discomfort, visceral sensations associated with bodily processes like breathing or digestion, or sensations associated with physiological arousal. As with the other forms of RT, uncontrollability, negative valence, and seeking (vs. solving) purpose characterize interoceptive RT (Ginzburg et al., ; Witthöft et al., ). Temporally, we would expect interoceptive RT to be present focused, with an orientation toward current bodily sensations (Wittmann, ).…”
Section: The Defining Features Of Maladaptive Rtmentioning
confidence: 99%
See 1 more Smart Citation
“…These central processes might be related to neural refractoriness (Truini et al, 2007) or to attention-and arousal-specific mechanisms triggered by the novelty and temporal predictability of the painful stimuli (Wang et al, 2010). It has been also argued in previous studies that central habituation may reflect a neurocognitive effort to suppress pain that is below the damage threshold, in order to leave more cognitive resources for dealing with more biologically relevant stimuli (Bingel et al, 2007;Ginzburg et al, 2015). In the case of repeated high-intensity pain stimuli, the optimal behavioural response is thought to be dominated by sensitization (Woolf, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…To achieve correct and accurate body awareness depends on the integration the afferent proprioception from joints and muscles. Body awareness copes with problems by identifying the changes in their bodies and experiencing and accepting the changes [1,2]. Some researchers reported that there is a dissonance between accurate and estimated proprioception in patients with chronic pain [3][4][5].…”
Section: Introductionmentioning
confidence: 99%